CLUSTER ANALYSIS USING HIERARCHIC METHOD BASED ON HUMAN DEVELOPMENT INDICATORS OF DISTRICT/CITY IN BANTEN PROVINCE - Muhartini, Ajeng Afifah; Mahuda, Isnaini; Sukmawati, Sri; Agusutrisno, Agusutrisno (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2024)
Human Development Index is a measure of human development achievement based on a number of basic components from quality of life. Cluster analysis is a technique used to categorize objects into different groups from another groups. The purpose of this research is to classify districts/cities based on indicators of Human Development Index (HDI) with the hierarchic method in Banten Province. This research was conducted to determine the characteristics of each group based on HDI indicators in Banten Province. The data used is secondary data with the population are all regencies/cities in Banten Province which includes Tangerang City, South Tangerang City, Serang Regency, Pandeglang Regency, Lebak Regency, Tangerang Regency, Cilegon City and Serang City. Cluster analysis was carried out using single linkage, average linkage, and complete linkage methods. The results of the study obtained 2 clusters in each of these methods with different characteristics. The first cluster is a cluster with characteristics of District, while the second cluster is a cluster with characteristics of City. The conclusion from this research is that the characteristics of each first cluster have a lower average value than the second cluster